Japan's imports of technology - Jan Winiecki (Intereconomics, 1978)
There are important reasons why Japan's policy regarding imports of technology should find its place in the literature devoted to the economic development of Asia, Africa and Latin America. It is Japan which mastered to a highest degree the ability to subordinate technology imports to development requirements of the national economy, and even though the procedure and instruments of this policy, as well as its effects, were applied and obtained in different socio-cultural and educational settings, the possibility of drawing from Japan's experience by developing countries seems considerable.
Keywords: 330; Technology